Isolation and biochemical characterization of probiotic bacteria obtained from yogurt samples of Rajshahi and Chittagong divisions of Bangladesh and their antimicrobial activity against enteric pathogens - Hossain, KM; Barai, P; Rahman, SMM; Mazid, MF Al; Gazi, MS; Jalil, MA (Bangladesh Journal of Livestock Research, 2020)
Probiotics are generally live microorganisms which exert beneficial effects on human and animal health by improving the gastrointestinal microflora. Isolation and proper identification of probiotic bacteria are very much important for safe use in food and feed industry. With this perceptive, the aim of the present study was the isolation of probiotic bacteria and their biochemical characterization. In this study, ten probiotic Lactobacillus spp. was isolated and according to their morphological, physiological and biochemical assay, it was observed that all the isolated bacteria were rod shaped, gram positive, catalase negative, non-motile and coagulase positive which are an indicator of typical probiotic bacteria. Carbohydrate fermentation pattern and growth against inhibitory substances viz. pH 3.0, 0.3% bile, 0.1-0.4% phenol and 1-6% NaCl ensured the criteria for identification of the probiotic bacteria. All the isolated bacteria showed excellent growth against low pH (3.0) and bile (0.3%) in a 24 hour period of time. Isolated bacteria were tested for their antimicrobial activity against eight human and animal enteric pathogens and showed promising antimicrobial efficacy against the selective pathogens. Further research regarding, molecular characterization and identification of specific genes and proteins of interest through technological intervention may help to develop next generation bacteriocins and industrially important drug for human and animals. Bangladesh J. of Livestock Res. 21-25: 142-152, 2018